Inhibiting prepotent responses in the elderly: Distraction and disinhibition. - Hsieh, Shulan; Wu, Mengyao; Tang, Chien-Hui (Cognitive, Affective & Behavioral Neuroscience, 2016)
In this study, we aimed to examine whether older adults, relative to younger adults, suffer from generic inhibition, selective inhibition, and/or distraction deficits, as assessed by behavioral and electrophysiological measures in a go/no-go task paradigm that included manipulations of no-go stimulus type (irrelevant vs. conflict) and no-go probability. A total of 96 individuals were recruited; each of three experiments included 32 participants (16 adults above and 16 adults below 60 years of age). The older adults performed more poorly than the younger adults in our behavioral test; however, the event-related potential results showed that irrelevant and conflict no-go stimuli incurred different processes that were differentially impacted by aging, as was reflected in the N2 and P3. That is, the older adults' inhibition deficits might be due to different underlying mechanisms: disproportionate processing of irrelevant no-go stimuli, and disproportionate suppression of conflicting information when executing or withholding a response to conflict no-go stimuli. The present results therefore support the theories of age-related selective inhibition and distraction deficits.